DMS Analyzer V.1 ... - Burke, Gabrielle; Wongpan, Pat (Zenodo, 2024)
This script was developed, using the BEPSII Sea Ice Core Analyzer (Vancoppenolle, 2017) as a template, to facilitate the processing of large numbers of sea ice cores, snow and seawater samples from the dataset ‘Collation of DMS and DMSP in Antarctic Snow, Sea ice and Underlying Seawater’, publicly available at the Australian Antarctic Data Centre (https://data.aad.gov.au/metadata/DMS_DMSP_Antarctica_Snow_Ice_Seawater_DataCollation). This dataset was compiled from historical measurements of Dimethylsulfide (DMS) and Dimethylsulfoniopropionate (DMSP) in Antarctic snow, sea ice and underlying seawater, following similar efforts by (Lannuzel et al., 2016) and (Meiners et al., 2012) for iron and chlorophyll-a, respectively, using a template from the Antarctic Sea ice Processes and Climate (ASPeCt)-Bio program. Due to the nature of the data, this database is comprised of Excel spreadsheets that each correspond to an individual core, or snow or water sample. The DMS Analyzer script allows users to easily extract ...